Pengaruh Metode Ekstraksi Terhadap Rendemen Dan Kadar Fenolik Ekstrak Tanaman Kayu Beta-Beta (Lunasia amara Blanco): (The Effect of Extraction Method on Yield Value and Phenolic Content of Beta-Beta (Lunasia amara Blanco) Bark Extract - Hasnaeni, Hasnaeni; usman, suriati; Wisdawati, Wisdawati (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
Lunasia amara Blanco bark belonging to the family Rutaceae. The research aimed to determine the effect of extraction method on yield value and phenolic content of bark extract of Lunasia amara Blanco by UV-Vis spectrophotometry. Sample was extracted by maceration, reflux, and soxhlet using methanol 70%. The extraction by maceration obtained the yield value of methanol extract of 2,352%; the reflux method of 1,611%; and the soxhlet method of 0,960%. Then the chemical content was identified by the addition of FeCl3 reagent and a blackish green color was formed positively indicating phenolic content. Afterward, phenolic identification was conducted by TLC with eluent n-hexane: ethyl acetate (2:8) containing phenolic because the Rf value was the same as the galic acid standard. The results showed that the extraction method producing the highest yield of bark extract of Lunasia amara Blanco was maceration. The phenolic content obtained by maceration was 66,548 mgGAE/g extract with 6.6548% GAE; the reflux was 73.645 mgGAE/g extract with 7.3645% GAE; and the soxhlet was 74.806 mgGAE/g extract with 7.4806% GAE.